Fifty shades of hatred and discontent: Varieties of anti-finance discourses on the European Twitter (France, Germany, Italy, Spain and the UK) - Elsa Clara Massoc (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Are we in a new "Polanyian moment"? If we are, it is essential to examine how "spontaneous" and punctual expressions of discontent at the individual level may give rise to collective discourses driving social and political change. It is also important to examine whether and how the framing of these discourses may vary across political economies. This paper contributes to this endeavor with the analysis of anti-finance discourses on Twitter in France, Germany, Italy, Spain and the UK between 2019 and 2020. This paper presents three main findings. First, the analysis shows that, more than ten years after the financial crisis, finance is still a strong catalyzer of political discontent. Second, it shows that there are important variations in the dominant framing of public anti-finance discourses on social media across European political economies. If the antagonistic "us versus them" is prominent in all the cases, the identification of who "us" and "them" are, vary significantly. Third, it shows that the presence of far-right tropes in the critique of finance varies greatly from virtually inexistent to a solid minority of statements.
urn:nbn:de:hebis:30:3-640403
Keywords: 330; finance; opinion; social media; discourse analysis